Impact of Village Governance, Security, Social Factors, and Infrastructure on Tourism Village Sustainability - Abduh, Muhammad; Destiny Sinaga , Rika (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2026)
This study examines the influence of village governance, security, social variables, and infrastructure on the sustainability of tourism villages in South Sumatra, Indonesia, solving a significant research gap in the comprehension of rural tourism development dynamics. The study seeks to assess the influence of these elements on sustainable practices in tourism villages, especially in regions facing socio-economic difficulties. A mixed-methods approach was employed, utilizing bivariate and multivariate logistic regression analyses on data from the Indonesian Village Potential Census (Podes) 2021. Critical findings indicate that competent governance, strong security frameworks, social capital, and infrastructure, including communication and transportation services, substantially improve village sustainability. Nonetheless, obstacles like as governance discrepancies and inadequate security persist. This research highlights the necessity for robust governance structures, community engagement, and infrastructure investments to guarantee sustainable tourism in the long term. Future strategies must prioritize the rectification of these deficiencies to bolster the resilience of tourism settlements.